Novel Drug Delivery System for Curcumin: Implementation to Improve Therapeutic Efficacy against Neurological Disorders - Mohi-ud-din, Roohi; Mir, Reyaz H.; Wani, Taha Umair; Shah, Abdul Jalil; Mohi-Ud-Din, Ishtiyaq; Dar, Mudasir Ahmad; Pottoo, Faheem Hyder (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Curcumin, a hydrophobic polyphenolic compound present in Curcuma longa Linn. (Turmeric), has been used to improve various neurodegenerative conditions, including Amyotrophic lateral sclerosis, multiple sclerosis, Parkinson's disease, Prion disease, stroke, anxiety, depression, and ageing. However, the Blood-Brain Barrier (BBB) impedes the delivery of curcumin to the brain, limiting its therapeutic potential. Objective/Aim: This review summarises the recent advances towards the therapeutic efficacy of curcumin along with various novel strategies to overcome its poor bioavailability across the bloodbrain barrier. Methods: The data for the compilation of this review work were searched in PubMed Scopus, Google Scholar, and Science Direct. Results: Various approaches have been opted to expedite the delivery of curcumin across the blood-brain barrier, including liposomes, micelles, polymeric nanoparticles, exosomes, dualtargeting nanoparticles, etc. Conclusion: The review also summarises the numerous toxicological studies and the role of curcumin in CNS disorders.
Keywords: neurodegenerative disease